Use of hydrogel scaffolds to develop an in vitro 3D culture model of human intestinal epithelium. (15th October 2017) - Dosh, R.H.; Essa, A.; Jordan-Mahy, N.; Sammon, C.; Le Maitre, C.L.
Graphical abstract: Abstract: The human intestinal cell lines: Caco-2 and HT29-MTX cells have been used extensively in 2D and 3D cell cultures as simple models of the small intestinal epithelium in vitro . This study aimed to investigate the potential of three hydrogel scaffolds to support the 3D culture of Caco-2 and HT29-MTX cells and critically assess their use as scaffolds to stimulate villi formation to model a small intestinal epithelium in vitro . Here, alginate, l -pNIPAM, and l -pNIPAM-co-DMAc hydrogels were investigated. The cells were suspended within or layered on these hydrogels and maintained under static or dynamic culture conditions for up to 21 days. Caco-2 cell viability was increased when layered on the synthetic hydrogel scaffolds, but reduced when suspended within the synthetic hydrogels. In contrast, HT29-MTX cells remained viable when suspended within or layered on all 3D cultures. Interestingly, cells cultured in and on the alginate hydrogel scaffolds formed multilayer spheroid structures, whilst the cells layered on synthetic hydrogels formed villus-like structures. Immunohistochemistry staining demonstrated positive expression of enterocyte differentiation markers and goblet cell marker. In conclusion, l -pNIPAM hydrogel scaffolds supported both cell lines and induced formation of villus-like structures when cells were layered on and cultured under dynamic conditions. The ability of the l -pNIPAM to recapitulate the 3D structure and differentiate main cell types of human intestinal villi may deliver a potential alternative in vitro model for studying intestinal disease and for drug testing. Statement of Significance: Forty percent of hospital referrals are linked to disorders of the digestive tract. Current studies have utilised animal models or simple cultures of isolated cells which do not behave in the same manner as human intestine. Thus new models are required which more closely mimic the behaviour of intestinal cells. Here, we tested a number of scaffolds and conditions to develop a cell culture model which closely represents the 3D environment seen within the human small intestine. We successfully created structures seen within the intestine which have not previously been possible with other culture models. These models could be used to investigate tissue engineering, drug discovery, and used as an alternative to in vivo animal models in drug toxicity studies.